RELATIONSHIP BETWEEN SELF-REGULATED LEARNING AND TASK AVERSIVENESS WITH ACADEMIC PROCRASTINATION IN HIGH SCHOOL STUDENTS IN THE AFFIRMATION PROGRAM FOR SECONDARY EDUCATION - Soumilena, Jequelin Ribka Lorohoema; Widyorini, Endang; Eryani, Praharesti (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
Procrastination is the habit of purposeful delay and the avoidance of tasks that are inherently unnecessary. In the realm of education, this behavior is identified as academic procrastination. This study aims to examine the relationship between self-regulated learning, task aversiveness, and academic procrastination among high school students enrolled in the Affirmative Education Program (abbreviated into: ADEM). The hypotheses of the study are as follows: 1) Major Hypothesis: There is a relationship between self-regulated learning and task aversiveness with academic procrastination among ADEM students; 2) First Minor Hypothesis: There is a negative relationship between self-regulated learning and academic procrastination among ADEM students; 3) Second Minor Hypothesis: There is a negative relationship between task aversiveness and academic procrastination among ADEM students. Participants in this research were 44 eleventh and twelfth-grade ADEM students selected through Incidental Sampling technique. Data collection involved the use of scales measuring academic procrastination, self-regulated learning, and task aversiveness. Data analysis included the application of the double correlation analysis technique to test the major hypothesis and the Product Moment analysis to test the minor hypotheses. The results reveal a correlation coefficient (R= 0.732, p<0.01) between self-regulated learning, task aversiveness, and academic procrastination, supporting the acceptance of the major hypothesis. Furthermore, the analysis of the first minor hypothesis indicates a significant negative relationship between self-regulated learning and academic procrastination (rx1y = 0.645, p<0.01), while the second minor hypothesis shows a significant negative relationship between task aversiveness and academic procrastination (rx2y= 0.698, p<0.01). In conclusion, the minor hypotheses of the study are accepted.